Penggunaan Media Peragaan Gambar dalam Pembelajaran Kreatif Menggambar Ilustrasi di Kelas IV Sekolah Dasar - - Sumanto (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: The purpose of this classroom action research was to describe teaching media types, students’ creativity improvement, and teachers’ capability improvement in teaching illustration drawing. Location of the research was   State Elementary School 02 Malang city. The data was collected by participation observation and documentation  (design, media, process, and teaching achievement). The collected data was analysed by descriptive qualitative. Results found: improvement of teaching quality; students skills and creativity increased; teachers capabilities in planning, implementation, reflection technique in teaching with picture media also increased.